Validation of Three-Dimensional Ray-Tracing Algorithm for Indoor Wireless Propagations - Salem, Majdi; Ismail, Mahamod; Misran, Norbahiah (ISRN Communications and Networking, 2011)
A 3D ray tracing simulator has been developed for indoor wireless networks. The simulator uses geometrical optics (GOs) to propagate the electromagnetic waves inside the buildings. The prediction technique takes into account multiple reflections and transmissions of the propagated waves. An interpolation prediction method (IPM) has been proposed to predict the propagated signal and to make the ray-tracing algorithm faster, accurate, and simple. The measurements have been achieved by using a single Wi-Fi network access point as a transmitter and a laptop as a receiver. Measured data had been collected at different positions in indoor environment and compared with predicted signals. The comparison of the predicted and measured received signals gave root mean square error of 2.96 dB and std. deviation of 2.98 dB.